Functional Consequences of the SCN5A-p.Y1977N Mutation within the PY Ubiquitylation Motif: Discrepancy between HEK293 Cells and Transgenic Mice - Simona Casini (International Journal of Molecular Sciences, 2019)
Dysfunction of the cardiac sodium channel Nav1.5 (encoded by the SCN5A gene) is associated with arrhythmias and sudden cardiac death. SCN5A mutations associated with long QT syndrome type 3 (LQT3) lead to enhanced late sodium current and consequent action potential (AP) prolongation. Internalization and degradation of Nav1.5 is regulated by ubiquitylation, a post-translational mechanism that involves binding of the ubiquitin ligase Nedd4-2 to a proline-proline-serine-tyrosine sequence of Nav1.5, designated the PY-motif. We investigated the biophysical properties of the LQT3-associated SCN5A-p.Y1977N mutation located in the Nav1.5 PY-motif, both in HEK293 cells as well as in newly generated mice harboring the mouse homolog mutation Scn5a-p.Y1981N. We found that in HEK293 cells, the SCN5A-p.Y1977N mutation abolished the interaction between Nav1.5 and Nedd4-2, suppressed PY-motif-dependent ubiquitylation of Nav1.5, and consequently abrogated Nedd4-2 induced sodium current (INa) decrease. Nevertheless, homozygous mice harboring the Scn5a-p.Y1981N mutation showed no electrophysiological alterations nor changes in AP or (late) INa properties, questioning the in vivo relevance of the PY-motif. Our findings suggest the presence of compensatory mechanisms, with additional, as yet unknown, factors likely required to reduce the “ubiquitylation reserve” of Nav1.5. Future identification of such modulatory factors may identify potential triggers for arrhythmias and sudden cardiac death in the setting of LQT3 mutations.